Whose Culture Is Represented? Multiculturalism and Diversity in Indonesian Primary English Textbooks - Andri Maulana; Smriti Singh (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examined the representation of culture, multiculturalism, and diversity in Indonesian primary school English textbooks titled: My Next Word, Grades 1-6, published by the Centre for Curriculum and Books under the Ministry of Education, and how these textbooks promote cultural diversity and intercultural communication as an international language. Given the importance of developing multicultural awareness through early English education and strengthening intercultural communication in the globalised world, this analysis provided critical insight into how such objectives are reflected in textbook content. The study employed a qualitative research approach and content analysis to explore multicultural values (textual and visual) in Indonesian elementary English textbooks. Addressing the lack of comparative, multi-grade (Grades 1–6) analyses of textual and visual cultural content in elementary English textbooks, this study applied a theoretical framework that conceptualises language as an artefact: a system of codes (products) representing cultural thought (perspectives), communication (practices), and social actors (persons). Findings revealed that multicultural values in the image analysis of six textbooks (Grades 1-6) are more prevalent in Grades 1-3 than in Grades 4-6. Moreover, textbooks highlighted local traditions, predominantly featured certain cultures representative, and lacked sufficient representation of Indonesia’s broader cultural and religious diversity. Additionally, global cultural representation was minimal. The study recommends a more balanced inclusion of local and international cultures in future textbooks.